Dialing in on pharmacological features for a therapeutic antioxidant small molecule - Green, Kayla N. (Dalton Trans, 2019)
The pyridinophane molecule L2 (3,6,9,15-tetraazabicyclo[9.3.1]penta-deca-1(15),11,13-trien-13-ol) has shown promise as a therapuetic for neurodegenerative diseases involving oxidative stress and metal ion misregulation. Protonation and metal binding stability constants with Mg(2+), Ca(2+), Cu(2+), and Zn(2+) ions were determined to further explore the therapeutic and pharmacological potential of this water soluble small molecule. These studies show that incorporation of an –OH group in position 4 of the pyridine ring decreases the pI values compared to cyclen and L1 (3,6,9,15-tetraazabicyclo[9.3.1]penta-deca-1(15),11,13-triene). Furthermore, this approach tunes the basicity of the tetra-aza macrocyclic ligand through the enhanced resonance stabilization of the –OH in position 4 and rigidity of the pyridine ring such that L2 has increased basicity compared to previously reported tetra-aza macrocycles. A metal binding preference for Cu(2+), a redox cycling agent known to produce oxidative stress, indicates that this would be the in vivo metal target of L2. However, the binding constant of L2 with Cu(2+) is moderated compared to cyclen due to the rigidity of the ligand and shows how ligand design can be used to tune metal selectivity. An IC(50)=298.0 µM in HT-22 neuronal cells was observed. Low metabolic liability was determined in both Phase I and II in vitro models. Throughout these studies other metal binding systems were used for comparison and as appropriate controls. The reactivity reported to date and pharmacological features described herein warrant further studies in vivo and the pursuit of L2 congeners using the knowledge that pyridine substitution in a pyridinophane can be used to tune the structure of the ligand and retain the positive therapeutic outcomes.